1997
DOI: 10.1007/s001340050288
|View full text |Cite
|
Sign up to set email alerts
|

Continuous venovenous haemofiltration using polyacrylonitrile filters does not activate contact system and intrinsic coagulation pathways

Abstract: The contact system was not activated further by continuous venovenous haemofiltration using polyacrylonitrile filters in critically ill patients. Premature clotting of the haemofilter circuit was more common in patients with very low levels of antithrombin III and heparin co-factor II; although this was related to thrombin generation, the intrinsic coagulation pathway does not appear to be implicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 23 publications
(18 reference statements)
2
49
0
4
Order By: Relevance
“…Standard laboratory tests of coagulation were normal and did not change with haemodialysis, which is in keeping with previous studies [17]. Thrombin times were marginally elevated pre-dialysis, but did not increase further.…”
Section: Discussionsupporting
confidence: 73%
“…Standard laboratory tests of coagulation were normal and did not change with haemodialysis, which is in keeping with previous studies [17]. Thrombin times were marginally elevated pre-dialysis, but did not increase further.…”
Section: Discussionsupporting
confidence: 73%
“…In a study of critically ill hemofiltered patients [5], we found that premature clotting of the filter circuit occurring within the first 24 h was associated with low baseline levels of AT-III and heparin cofactor II. Only in these patients did thrombin-antithrombin complex antibodies rise significantly, representing evidence of thrombin generation.…”
Section: Introductionmentioning
confidence: 99%
“…Critical illness may also result in an inflammatory response; contact activation occurs in intensive care patients 21,22 . However, an observational study of twelve intensive care patients undergoing haemofiltration failed to show contact activation 23 . Contact activation may therefore be more related to an inflammatory response than exposure of blood to a 'foreign' surface of an extracorporeal circulation.…”
Section: Relevance To Intensive Carementioning
confidence: 99%